Impact of temperature changes to the adhesion strength of molar tubes: an in vitro study - Benedikta Palesik; Kotryna Šileikytė; Julius Griškevičius; Rimantas Stonkus; Antanas Šidlauskas; Kristina Lopatienė (BMC, 2022)
Abstract Background The main purpose of this was to determine study adhesion strength of molar tubes bonding with a composite adhesive after exposure to a sudden change in temperature (thermal cycles). Methods The study sample consisted of 40 recently extracted human first permanent molars, which were randomly divided into two groups of 20: group 1 was the experimental group (affected by thermal cycles), and group 2 was the control group. Molar tubes were bonded with a light-cure tube adhesive. The experimental group teeth were dipped 2,000 times in saline at 5 °C and at 55 °C. The control group were immersed in 37 °C saline. Molar tubes for both groups were removed with an adapted Mecmesim Multitesters 2.5-I, and the data were recorded with EMPEROR software. ANOVA was used to calculate and compare the results. Results In the experimental group of the teeth, the maximum force was obtained at 94.2 N and the lowest force was 19.69 N. In the control group of the teeth, the maximum force was obtained at 159.1 N and the lowest force was 28.1 N. In the experimental group, the mean debonding force (59.12 N) was statically significantly smaller than in the control group (79.88 N), p = 0.0345. The forces in the control group were by 1.35 times greater than those in the experimental group. Conclusions The forces of the adhesion of molar tubes to the tooth surface were reduced after exposure to a sudden change in temperature (thermal cycles). The results were significantly different between the experimental group and the control group.